Pengujian Regresi Otomasi pada Aplikasi Mobile Satudikti Menggunakan Katalon Studio - Akram, Abdullah; Pratiwi, Nunik (Program Studi Teknik Informatika Universitas Pamulang, 2023)
Satudikti is a one-stop application from the many services available at the Directorate General of Higher Education, to make it easier for users to access various higher education services in one application. Before the application can be widely used, a testing step is indispensable. This is due to potential problems in higher education data that can have a fatal impact, considering that this data is closely related to state information. And if there is an error in the software, the Directorate General of Higher Education must restart the development process that can harm the state. Therefore, the purpose of this study is to test the readiness of the application when it is widely used and reduce the risk of errors to ensure that the application remains of sufficient quality for users, as well as analyze the effectiveness of the application and then whether automated regression testing using Katalon Studio has more value than manual testing. Testing in this study was carried out manually with the black-box testing method and automated testing using Katalon Studio as an automated testing tool. Testing using Katalon Studio found that the functionality, features, and access to the tested pages worked well according to existing requirements. The implementation of automation testing using Katalon Studio has also proven to be more efficient in reducing test time and providing detailed test results to detect errors with easy-to-understand reporting.